Pre-Liposomes: A novel drug delivery system - Sheth, Maitry; Jadhav, Divya; Jain, Hitesh; Meshram, D. B. (Journal of Drug Delivery and Therapeutics, 2019)
Preliposomes are a novel drug delivery system (NDDS). Preliposomes, due to their various forms, require further exploration. These structures can deliver both hydrophilic and hydrophobic drugs for cancer, bacterial infections, fungal infections, immunomodulation, diagnostics, ophthalmic, vaccines, enzymes and genetic elements. Prevesicular drug delivery system like preliposomes having distinct advantages over conventional drug delivery system. These systems overcome the problems associated with instability of liposomes. preliposomes composed of water-soluble porous powder as carrier which having ability to rapid hydration of preliposomes and formed vesicles. New concept of demonstrating preliposomes as novel carrier to enhance the oral bioavailability and permeation across the membrane. On the basis of investigation. it is clear that pre-liposomes are the alternate drug carrier for the various route of administration. These reviews give the brief knowledge about the preparation, evaluation and application of prevesicular drug delivery system in pharmaceutical field. The current deepening and widening of liposome interest in many scientific disciplines and their application in pharmaceutics, cosmetics and food industries as promising novel breakthroughs and products are also handle. The obtained information allows establishing criteria for selecting pre-liposomes as a drug carrier according to its advantages and limitations. Keywords: Novel drug delivery, Liposomes, Lamellar, Carrier